2016
DOI: 10.1111/saje.12138
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Industrial Cluster Formation Through the Realistic Export Opportunities of the TRADE‐DSM

Abstract: This paper explores the natural synergies between industrial cluster formation and the identification of realistic export opportunities (REOs), using the TRADE‐DSM for a resource‐dependent region, the North West Province of South Africa. The structural path analysis and power of pull methods were applied to a provincial social accounting matrix to identify the top industrial clusters. Ten industrial clusters were identified and matched to the results of the TRADE‐DSM. Six of the industrial clusters analysed ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…On the one hand, many studies showed that students' attitude toward science and their science achievement correlated positively and moderately (Nolen, 2003 ; Mungin, 2012 ; Ng et al, 2012 ; Hacieminoglu, 2016 ; Chi et al, 2017 ; Wang and Liou, 2017 ; Zheng et al, 2019 ). For instance, based on the data from Program for International Student Assessment (Pisa et al, 2017 ), the study conducted by Chi et al ( 2017 ) pointed out that students' interest, enjoyment, and the perceptions of general value in science were positively correlated with scientific competencies. Similarly, in another study with 537,170 15-year-old students, Zheng et al ( 2019 ) stated that students' interest in science was positively associated with their science achievement.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, many studies showed that students' attitude toward science and their science achievement correlated positively and moderately (Nolen, 2003 ; Mungin, 2012 ; Ng et al, 2012 ; Hacieminoglu, 2016 ; Chi et al, 2017 ; Wang and Liou, 2017 ; Zheng et al, 2019 ). For instance, based on the data from Program for International Student Assessment (Pisa et al, 2017 ), the study conducted by Chi et al ( 2017 ) pointed out that students' interest, enjoyment, and the perceptions of general value in science were positively correlated with scientific competencies. Similarly, in another study with 537,170 15-year-old students, Zheng et al ( 2019 ) stated that students' interest in science was positively associated with their science achievement.…”
Section: Introductionmentioning
confidence: 99%
“…This paper builds on previous work done on the identification of industrial clusters in the NWP (Pisa, 2014;Pisa et al, 2017). In -depth descriptions of the structural path analysis (SPA), and power of pull (PoP) methods have been described and published elsewhere (Pisa, 2014;Pisa et al, 2016). SPA sh ows how, in structural terms, an exogenous demand shock on the origin (transport) sector affects the destination sector (37 commodity sectors).…”
Section: Materials and Methods Datamentioning
confidence: 99%
“…As Bastos et al (2018, 357) observes "increasing exports to high income destinations may require quality upgrading of entire complexes of suppliers and downstream producers, not just of particular exporters." In this regard, Pisa et al (2017) investigates the link between export opportunity identification and pursuit and the strengthening of local industrial clusters in South Africa.…”
Section: What Is the Value Of Trade Facilitation?mentioning
confidence: 99%